An experimental investigation of the effect of multiple inlet restrictors on the heat transfer and pressure drop in a flow boiling microchannel heat sink. (June 2020) - Oudah, Saad K.; Fang, Ruixian; Tikadar, Amitav; Salman, Azzam S.; Khan, Jamil A.
Highlights: In this study, experimental investigations were performed to quantify the effect of different configurations of inlet restrictors on the heat transfer performance and pressure drop in a flow boiling microchannel heat sink. Multiple IRs performs best in CHF enhancement at low mass flux, and the 1IR case performs best at high mass flux. For lower mass flow rates, cases with multiple-opening inlet restrictors generally work better (e.g., higher CHF) than cases with the single-opening inlet restrictor. The optimum configuration was obtained by maximizing the heat transfer performance (e.g., in terms of CHF enhancement) and minimizing the pressure drop penalties. Abstract: Flow boiling instabilities inherent in microchannels / microgaps remain to be a serious issue in two-phase high-heat-flux cooling applications, as they cause significant oscillations in flow rate, temperature, pressure, reduction in heat transfer coefficient (HTC), and eventually early occurrence of critical heat flux (CHF). This study experimentally investigated the effects of various configurations of inlet restrictors (IRs) on the thermal hydraulic performance of flow boiling in a microchannel heat sink, which has a single rectangular microchannel with an aspect ratio of 13.12 and a hydraulic diameter of the 708 µm. The experiments were carried out for the microchannel with three designs of inlet restrictors: one-slot opening (1IR), three-slot openings (3IR), and five-slot openings (5IR), for mass fluxes of 32.68, 81.29 and 144 kg/m 2  s, respectively. The effects of the various IRs on the CHF, average HTC and pressure drops of the microchannel heat sink were analyzed. The results showed that all test cases with IRs improved the CHF performance of the flow boiling microchannel heat sink, where the 5IR case works best at low mass flux and the 1IR case works best at high mass flux. The results also illustrated that the IRs reduce the HTC at low mass flux, but improve the HTC at high mass flux and heat flux. IRs always exhibit higher pressure drop penalties. This study also revealed the optimum design for microchannel with IRs, which depends on the operational parameters (e.g., mass flux and heat flux) of the microchannel heat sink.